PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PADA CV. SUMARNI SITE PT.PAMAPERSADA NUSANTARA KECAMATAN MURUNG PUDAK KABUPATEN TABALONG - Taufik Rahman (Jurnal PubBis, 2019)
Motivation is a series of processes of human behavior in which this behavior can encourage someone to contribute to the organization with the aim of achieving the goals of the organization. After employees feel happy with their jobs, employees will respect the rights and obligations of fellow employees so that a conducive working atmosphere is created, in the end employees earnestly give their best ability in carrying out their duties and responsibilities, and this means that the maximum performance will shown by employees.The type of research used in this study is to use descriptive analysis with a quantitative approach and assisted with the GSCA program, this type of research is to obtain accurate information about the motivation of employees through performance evaluation by distributing questionnaires to employees to obtain accurate data.The results of testing the model using the GSCA test show that Motivation (X) has a significant effect on Performance (Y) obtained an estimate value of 0.681, with a CR of 3.18. The test results are significant, because CR> 1.96. While the magnitude of the contribution of the Motivation (X) variable to Performance (Y) is 54.9%, and the remaining 45.1% is influenced by other variables, such as Leadership Style, Incentives, Work Environment, and others. Keywords: Motivation, performance,